Pendapat para Ulama Kabupaten Gresik terhadap Penggunaan Uang Elektronik menurut Hukum Islam - Nabila Zulfatien Nisa’ Al-Uluwiyah; Moh. Faizur Rohman (Islamic Economic Law Programs, Faculty of Sharia and Law State Islamic University (UIN) of Sunan Ampel Surabaya., 2021)
This study aims to determine the opinion of the Ulama in Gresik Regency on the Use of Electronic Money according to Islamic Law. This field research uses a descriptive analysis method related to the views of the scholars of Gresik Regency on the use of electronic money. The data is then analysed using the Fatwa of the National Sharia Council (DSN) Number 116/DSN-MUI/IX/2017 concerning Sharia Electronic Money. Scholars in Gresik Regency stated that electronic money is only a modern payment tool in the card format that stores the money value in digital form. In general, electronic money can make it easier to use in all types of transactions, although it is not entirely reliable in terms of security. If the electronic money card is lost, the money value in the card will also be lost, and the owner cannot ask for accountability from any party. The scholars in Gresik Regency also stated that electronic money is halal and legal as long as it does not contain elements of gharar, is not used for things prohibited by religion. In purchasing electronic money, balances must be in the amount of cash paid so that usury does not occur. Thus this is also per the DSN-MUI Fatwa No. 116/DSN-MUI/IX/2017, which states that sharia electronic money is following sharia principles.